Dampak Komitmen Organisasi terhadap Kepuasan Kerja Pegawai pada Dinas Pendidikan dan Kebudayaan Kabupaten Aceh Utara - Zulfikar, Zulfikar (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2022)
Organizational commitment has a very large influence on employee job satisfaction, especially in terms of improving the quality of employee performance. Sometimes both the incumbents/staff do not heed the agreed commitments so as to allow a decrease in the quality of performance in an organizational unit. This study surveyed a large number of people, including employees working in North Aceh Education and Culture Offices. This research is quantitative research. Questionnaires were used to collect data. The non-probability sampling method is used to select respondents from a population. The analysis used in this study is multiple linear regression analysis. The result of this research is to increase the implementation of organizational commitment to increasing employee job satisfaction. This research is expected to be input and reference for leaders in developing policies related to organizational commitment to employee job satisfaction in an organization, and the results of this study cannot be used as a reference or comparison for an organization regarding the impact of organizational commitment on employee job satisfaction.